Analisa Kelayakan Investasi Perbaikan Sarana Produksi Pada Home Industri Kerupuk Bawang - Dyah Susanti, Herdiana (Jurnal Teknik Industri, 2012)
Onion Cracker has a unique onion is half maturation of the chewy dough and cut into thin hard, the pieces can be good just by using the slicer. The perpetrators of many home industry who complain that their profits can not be produced due to constraints on the maximum cutting process that is still traditional. It is therefore necessary process improvements to increase production capacity, as well as conducting a feasibility study. Based on market aspects, the replacement methods on a conventional blade cutting process of using a new cutting machine at UD. Kalirejo considered feasible because of the data currently available demand tends to increase significantly. Also from the technical aspects are considered feasible because of the output produced by using a new cutting machine is greater than the output using a conventional knife. Output of conventional blades = 60 Kg per day and a new cutting machine crackers = 100 Kg per day. As well as from the financial aspect considered feasible because of the newly acquired piece of machinery NPV Rp. 514 604 751, IRR of 65.88%, and DPP 2 years 11 months. Improvement in the cutting process feasible because the amount of income earned is greater than the cost of the investment program ROI 1,44.